2023
DOI: 10.3390/languages8010079
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences and Durations of Filled Pauses in Relation to Words and Silent Pauses in Spontaneous Speech

Abstract: Filled pauses (i.e., gaps in speech production filled with non-lexical vocalizations) have been studied for more than sixty years in different languages. These studies utilize many different approaches to explore the origins, specific patterns, forms, incidents, positions, and functions of filled pauses. The present research examines the presence of filled pauses by considering the adjacent words and silent pauses that define their immediate positions as well as the influence of the immediate position on fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…However, at age of 5 the most common turn-taking time-gaining means are filled pauses which later become hát 'well'. The use of turn-taking time-gainers appeared in all children, but their frequency and type differed between individuals; this is also in line with other research that has pointed to individual strategies in the areas of the use of disfluencies and discourse markers [2], [20].…”
Section: Filled Pauses and Discourse Markers At Turn-starting Positionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, at age of 5 the most common turn-taking time-gaining means are filled pauses which later become hát 'well'. The use of turn-taking time-gainers appeared in all children, but their frequency and type differed between individuals; this is also in line with other research that has pointed to individual strategies in the areas of the use of disfluencies and discourse markers [2], [20].…”
Section: Filled Pauses and Discourse Markers At Turn-starting Positionsupporting
confidence: 88%
“…[ǝm], [ǝh] and other forms [1], [2]. The occurrence of hesitations is related to the complexity of language planning and language production [3], and is also influenced by many other factors, such as speech type, gender, or individual characteristics [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…This confirms our third hypothesis. Gósy [15] found that the duration of filled pauses highly depends on the position of filled pauses, whether they are between two silent pauses or they are attached to a word. We didn't consider this factor, but a future avenue of research could be to examine whether the phonetic position of filled pauses changed as interpreter trainees progressed in their training.…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation is a stuttering-like disfluency (Costa, Ritto, Juste & Andrade, 2017) and it can be characterized as a sound (consonant or vowel) spoken with a larger duration than normally expected (Johnson, 1961), causing an inappropriate elocution duration, and it may be accompanied by pitch elevation (Yaruss, 1998). In the literature related to linguistics, the prolongation is called elongation or filled pauses (Betz & Kosmala, 2019;Gold, Ross, & Earnshaw, 2018;Defracq & Plevoets, 2018 ) and it is defined as a conversational marker (Betz & Kosmala, 2019;Bellinghausen, Fangmeier, Schröder, & Keller, 2019) until the utterance is complete (Betz & Kosmala 2019;Gósy, 2019), showing the end-of-shift indication, attention and confirmation of the listener (Gósy, 2019), related or not to difficulties that the speaker has in planning and formulating what is said. Some studies point to the presence of prolongation in the speech of the fluent individuals, regardless of age (Pinto, et al 2013;Rose & Watanabe, 2019;Andrade, & Martins, 2007;Götz, 2019;Andrade & Martins-Reis, 2011;Castro, Martins-Reis, Baptista, & Celeste, 2014;Silva, Fabron, Picoloto, & Oliveira, 2016;Nogueira, Oliveira, Giacheti, & Moretti-Ferreira, 2015;Natke, Sandrieser, Pietrosky, & Kalveram, 2006), reinforcing the prolongation being directed as a discursive marker (Betz & Kosmala, 2019;Bellinghausen et al, 2019;Gósy, 2019) that can be used as a strategic tool of the interlocutor in communication (Celeste & Reis, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature related to linguistics, the prolongation is called elongation or filled pauses (Betz & Kosmala, 2019;Gold, Ross, & Earnshaw, 2018;Defracq & Plevoets, 2018 ) and it is defined as a conversational marker (Betz & Kosmala, 2019;Bellinghausen, Fangmeier, Schröder, & Keller, 2019) until the utterance is complete (Betz & Kosmala 2019;Gósy, 2019), showing the end-of-shift indication, attention and confirmation of the listener (Gósy, 2019), related or not to difficulties that the speaker has in planning and formulating what is said. Some studies point to the presence of prolongation in the speech of the fluent individuals, regardless of age (Pinto, et al 2013;Rose & Watanabe, 2019;Andrade, & Martins, 2007;Götz, 2019;Andrade & Martins-Reis, 2011;Castro, Martins-Reis, Baptista, & Celeste, 2014;Silva, Fabron, Picoloto, & Oliveira, 2016;Nogueira, Oliveira, Giacheti, & Moretti-Ferreira, 2015;Natke, Sandrieser, Pietrosky, & Kalveram, 2006), reinforcing the prolongation being directed as a discursive marker (Betz & Kosmala, 2019;Bellinghausen et al, 2019;Gósy, 2019) that can be used as a strategic tool of the interlocutor in communication (Celeste & Reis, 2013). Despite these previous findings, prolongation is considered as a typical stuttering disorder in the speechlanguage literature (Costa et al 2017;Natke et al 2006;Campbell & Hill, 1998;Souza, Paschoalino, Cardoso & Oliveira, 2013;Tumanova, Zebrowsi, Throneburg & Kayikci, 2011).…”
Section: Introductionmentioning
confidence: 99%